Keratitis by Aspergillus flavus infection after cataract surgery - João Luiz Pacini Costa (Revista Brasileira de Oftalmologia)
ABSTRACT We report a case of keratis infection after cataract phacoemulsification with intraocular lens implantation in a 65-year-old female patient. The patient initially underwent cataract surgery on the right eye. Intraocular inflammation appeared on the second post-operative day and was initially treated as Toxic Anterior Segment Syndrome (TASS). The inflammation was reduced and vision improved initially but very aggressive and progressive keratitis destroyed the cornea due to the delay in correct diagnosis. Aspergillus flavus was isolated from a biopsy.The infection was treated with antifungal agents and loss of the eye was avoided by total corneal transplantation associated with Gundersen conjunctiva cover. To restore the lost vision, a second penetrating corneal graft with removal of the conjunctiva cover was performed 17 months later. The final best-corrected vision was 20/40 but prognosis for long-term graft survival is poor.